Polymorphism rs1799983 of the eNOS gene in patients with type 2 diabetes mellitus - Savicheva, Kateryna; Nesen , Andrii; Semenovykh , Polina (The Ukrainian Scientific Medical Youth Journal, 2024)
Nowadays diabetes mellitus is one of the most common non-communicable human diseases after cardiovascular and oncological pathology, leading to disability and death. Establishing the association of the rs1799983 polymorphism of the eNOS gene with the development and progression of diabetes mellitus and further assessment of individual genetic risk is important for the development of a differentiated approach to the prevention and treatment of this pathology and its complications, depending on the hereditary predisposition of a particular patient. The purpose of the study was to determine the prevalence of the rs1799983 polymorphism of the eNOS gene in patients with type 2 diabetes mellitus with nephropathy and to identify a possible association between the course of the disease and the genetic profile of the subjects. Materials and methods: 126 patients with diabetic nephropathy were examined during the study, and the control group consisted of 20 healthy individuals. Deoxyribonucleic acids were isolated from blood by the standard method using the NeoPrep50 reagent kit (Neogen, Ukraine). Genotyping of the rs1799983 polymorphism of the eNOS gene was performed by TaqMan technology using the Taq-Man® Fast Universal PCR Master Mix and TaqMan® SNP Assay. Statistical analysis of genetic associations was performed using the SNP Stats program. Results: in patients with type 2 diabetes mellitus with diabetic nephropathy, the distribution of genotypes was as follows: G/G - 63.5 %, G/T – 33,3 % і T/T – 3,2 %. The distribution of allelic variants in this group of patients was as follows: G allele - 80.2%, T allele - 19.8%. In the control group, according to the results of our study, the G/G genotype of the rs1799983 polymorphism of the eNOS gene was 85.0%, G/T - 10.0% and T/T - 5.0%. The frequency of the D allele was 90.0%, and the T allele was 10.0%. Data analysis using the online program SNPStats demonstrated a significant difference in the frequency of genotypes and alleles of the studied polymorphism in the group of patients with diabetic nephropathy compared with controls, which corresponds to the dominant model of inheritance of the HR 0.31 (0.09-0.99); p=0.045. Conclusions: in patients with diabetic nephropathy, the distribution of genotypes of the rs 1799983 polymorphism of the eNOS gene corresponded to the Hardy-Weinberg equilibrium in all studied groups and did not differ significantly from European populations. In the group of patients with type 2 diabetes with nephropathy, the total frequency of G/T and T/T genotypes of the eNOS gene was 3 times higher than in the control group, which proves the undeniable influence of the T allele on the development of kidney damage in this cohort of patients.